Ionic transport properties and their empirical correlations for thermal-to-electrical energy conversion. (July 2021) - Sohn, Ahrum; Yu, Choongho
Abstract: Thermal-to-electrical energy conversion due to the thermo-diffusion of ions is an emerging field of study, which has attracted significant research efforts over the past several years due to unprecedentedly large thermopower over several mV/K compared to 10 −2 –10 −1 mV/K from conventional electronic thermoelectric materials. Nevertheless, key enabling principles and general rules for achieving the extraordinary properties have yet to be fully unveiled due to the complexity in establishing consolidated theories unlike crystalline solids. Here we suggest empirical relationships between ionic conductivity and ionic thermopower as well as their dependency on relative humidity (RH). It is very intriguing to see both ionic electrical conductivity and ionic thermopower are simultaneously improved as RH is raised, in contrast to their adverse correlation in conventional electronic thermoelectrics, offering potential breakthroughs for large performance enhancement. This paper mainly focuses on the thermo-diffusion of ions called the Soret effect in solid-state polyelectrolytes due to their large thermopower, and their transport properties were described in comparison to electronic Seebeck effects. Representative materials and their device applications are introduced along with underlying physics and perspectives. We anticipate that this work serves as a guide for exercising their outstanding properties as well as opening up new strategies for thermal-to-electrical energy conversion. Graphical abstract: Image 1 Highlights: The thermo-diffusion of ions due to the Soret effect is introduced and summarized. Ionic conductivity and thermopower as a function of relative humidity are described. Empirical correlations between ionic thermoelectric properties are suggested. The largest possible thermoelectric responses and applications are presented.